The Relation of an International Student Center’s Orientation Training Sessions with International Students’ Achievement and Integration to University - Güvendir, Meltem Acar (Journal of International Students, 2018)
The purpose of the research is to examine the relation of orientation training sessions with integration and achievement of the international students. The study used the Institutional Integration Scales, developed by Pascarella and Terenzini (1980), to examine the integration level of the international students. 181 freshmen undergraduate and graduate international students who study at an American university filled out the scales in June 2015. According to the results, the scale’s factor scores vary depending on the frequency of using the center. The students’ GPA scores did not vary with regard to whether the students benefited from the center frequently or not. The study findings show that the frequency of using the center is important on integration to university.